Understanding collective action - Ostrom, Elinor (International Food Policy Research Institute, 2004)
The author tells us that Collective action occurs when more than one individual is required to contribute to an effort in order to achieve an outcome. People living in rural areas and using natural resources engage in collective action on a daily basis when they plant or harvest food together; use a common facility for marketing their products; maintain a local irrigation system or patrol a local forest to see that users are following rules; and meet to decide on rules related to all of the above. Frequently, however, it becomes difficult to exclude nonparticipants from benefiting from the collective action of others. This situation creates a collective action problem for the participants. When individuals seek out short-term benefits for themselves alone, they are better off when others contribute to the collective action and they do not. In this case, they benefit without paying the costs. Of course, if all individuals pursue short-term, self-centered benefits, no collective benefits are achieved. She then discusses how participants can overcome the collective action problems they face and the resource system attributes and the participant attributes that aid in overcoming these problems. -- from Text.